Thiazole Based Carbohydrazide Derivatives as α-Amylase Inhibitor and Their Molecular Docking Study - Muhammad Taha; Maryam Irshad; Syahrul Imran; Fazal Rahim; Manikandan Selvaraj; Noor Barak Almandil; Ashik Mosaddik; Sridevi Chigurupati; Faisal Nawaz; Nor Hadiani Ismail; Mohamed Ibrahim (Heteroatom Chemistry)
In this study we are going to present thiazole based carbohydrazide in search of potent antidiabetic agent as α-amylase inhibitors. Thiazole based carbohydrazide derivatives 1-25 have been synthesized, characterized by 1HNMR, 13CNMR, and EI-MS, and evaluated for α-amylase inhibition. Except compound 11 all analogs showed α-amylase inhibitory activity with IC50 values from 1.709 ± 0.12 to 3.049 ± 0.25 μM against the standard acarbose (IC50 = 1.637 ± 0.153 μM). Compounds 1, 10, 14, and 20 exhibited outstanding inhibitory potential with IC50 value 1.763 ± 0.03, 1.747 ± 0.20, 1.709 ± 0.12, and 1.948 ± 0.23 μM, respectively, compared with the standard acarbose. Structure activity relationships have been established for the active compounds. To get an idea about the binding interaction of the compounds, molecular docking studies were done.